Epistemologi Pembelajaran Mandiri dalam Penguasaan Qawa’id Bahasa Arab di Era Digital - Safira Ika Nur’Aini; M. Yunus Abu Bakar; Oktavia Ratnaningtyas (Kartika: Jurnal Studi Keislaman, 2026)
The development of digital technology has fundamentally transformed the practice of learning Arabic qawāʿid (grammatical rules), shifting the pattern from teacher-centered transmission toward reflective and contextual independent knowledge construction. This article examines self-directed learning in mastering qawāʿid from an epistemological perspective, focusing on three main dimensions: how knowledge is acquired, the sources of knowledge, and the mechanisms for validating grammatical correctness in the digital era. Using a descriptive qualitative approach through literature review and philosophical epistemological analysis, the findings show that broad access to digital sources positions learners as active epistemic subjects. They are no longer merely recipients of knowledge but are able to access, manage, test, and reflect on grammatical rules independently through critical interaction with various digital platforms. Self-directed learning represents a fundamental epistemological shift: from learning dependent on external authority toward a process of critical thinking and continuous knowledge construction. Thus, self-directed learning serves a dual function, namely as both a pedagogical strategy and an epistemic process that shapes ways of knowing, making it relevant and essential in forming autonomous, critical, and adaptive Arabic language learners amidst the continuously evolving digital landscape.